Comparison of Basal and Clomiphene Citrate Induced FSH and Inhibin B, Ovarian Volume and Antral Follicle Counts as Ovarian Reserve Tests and Predictors of Poor Ovarian Response in IVF - Erdem, Mehmet (Kluwer Academic Publishers-Plenum Publishers, 2004)
Purpose: To compare basal and clomiphene citrate (CC) induced follicle-stimulating hormone (FSH), estradiol (E(2)), and inhibin B levels with ultrasound indices of ovarian reserve in infertile women and to test the prognostic value of these tests on response to ovarian stimulation in in vitro fertilization (IVF). Methods: Fifty-six patients had basal and CC induced serum hormone levels and ultrasound measured mean ovarian volume (MOV) and mean antral follicle counts (MFC). Thirty-two patients were then appropriately selected to have a total of 41 cycles of IVF/ICSI treatment. Results: Women with diminished ovarian reserve had lower MOV, MFC, day 3 and day 10 inhibin B levels (p< 0.001). Only basal and CC induced FSH and inhibin B correlated with MOV and MFC. Poor responders in IVF/ICSI had higher basal FSH (p< 0.05), lower basal and induced inhibin B levels (p< 0.05), and lower MOV and MFC (p< 0.01) than normal responders. Ovarian volume alone was better than age and basal hormones in predicting poor ovarian response, while abnormal CC test was the only independent significant factor in predicting ovarian response. However, age was the only independent predictor of pregnancy in IVF as compared to hormonal and ultrasound indices of ovarian reserve. Conclusion: CC test and ovarian volume are better than other hormonal and sonographic tests in predicting the response to ovarian stimulation in IVF cycles.